Design and Control of a STATCOM for Non-Linear Load Compensation: A Simple Approach - Tripathi Saurabh Mani; Barnawal Prakash Ji (Electrical, Control and Communication Engineering)
This paper presents a systematic procedure to design a simple control for a three-phase VSC-based static synchronous compensator (STATCOM) in order to overcome the problems caused by the presence of the non-linear load at the point of common coupling (PCC). The proposed control method regulates the STATCOM in such a way that the source quadrature current component is forced to be zero so that only the active current component is drawn from the source and the harmonic and reactive current demands of the non-linear load are met by the STATCOM. The tuning of the inner and outer loop PI controllers is carried out with the help of the modulus optimum and symmetric optimum criteria, respectively. At last, a few case studies are presented using MATLAB simulation to exemplify the success of the proposed control method.